EVALUATION OF THE ANALGESIC AND ADVERSE EFFECTS OF TRAMADOL IN COMBINATION WITH LOW DOSE BUPIVACAINE FOR PAINLESS EPIDURAL DELIVERY: Painless Epidural Delivery - Rao, Surg Capt Zahid Akhtar; Ehsan ul Haq, Muhammad; Ali, Liaqat (Pakistan Armed Forces Medical Journal, 2010)
Objective: To evaluate the analgesic and adverse effects of Tramadol in combination with low dose Bupivacaine for painless epidural delivery.Study Design: Quasi-experimental study.Place and Duration of Study: The study was carried out at department of anaesthesiology Military Hospital Rawalpindi from August 2004-July 2007.Material and Methods: Fifty ASA-I uncomplicated full term primiparous were selected. Epidural analgesia was given with 15ml of 0.1% Bupivacaine plus 0.5% Tramadol when labour was established and was repeated on patient’s demand. Pain was assessed by using verbal analogue scale 0-10 in first stage as well as in second stage of labour. Adverse effects on mother and baby were noted. Overall satisfaction about the procedure was also assessed.Results: Forty two (84%) rated first stage of labour pain free (VAS-0) and Eight patients (16%) rated it as good pain relief (VAS-3). Thirty four (68%) patients in second stage of labour rated it pain free while sixteen (32%) patients rated it as good pain relief (VAS-3). One patient developed hypotension. Two patients complained of nausea. No patient complained of vomiting and none of them developed sedation. Three (6%) newborns had Apgar score nine and forty seven (94%) had ten after five minutes of delivery. Forty four patients described the experience as excellent; five described it as good and one as satisfactory.Conclusion: Tramadol used in epidural painless delivery in combination with low dose Bupivacaine is very effective analgesic with less adverse effects on mother and baby and can be used as an alternative to fentanyl/pethedine.